Boron nutrition increase soybean seed yield and maintain the quality of germination in storage seeds - Rodrigues, Dágila Melo; Campos, Cid Naudi Silva; de Souza Junior, Jonas Pereira [UNESP]; Alves, Charline Zaratin; da Silva Cândido, Ana Carina; Teodoro, Larissa Pereira Ribeiro; Teodoro, Paulo Eduardo; Coradi, Paulo Carteri; de David, Carlos Henrique Oliveira; de Mello Prado, Renato [UNESP] (Springer Nature, 2024)
Boron (B) nutrition can contribute to the conservation of seed quality during storage. Thus, it is crucial to investigate which source and amount of B applied to the soil is most suitable to increase the yield and maintain the quality of germination and carbohydrate content in soybean seeds during 180 days of storage. The cultivar Bonus 8579 Ipro® was evaluated in a field experiment in a 5 × 2 factorial scheme, with five B doses: 0, 1, 2, 4 and 8 kg ha−1, and two sources: boric acid and ulexite, arranged in randomized block design with three replicates. After harvest, the B content and accumulation of B in yield and seed quality were analyzed. Subsequently, the seeds were stored in a cold chamber at 17 °C and controlled relative humidity of 20% for 180 days. Soybean plants responded positively to the boric acid and ulexite with an increase in yield and seed quality up to the doses of 3.17 and 3.36 kg ha−1 of B, respectively. Furthermore, both sources potentiated the carbohydrate content in the seeds over the storage time. Our findings reveal that the application from 3.2 to 4.0 kg ha−1 of B using boric acid maintains high seed germination after 180 days of storage.
Keywords: Boric acid; Plant nutrition; Seed physiology; Seed stored; Ulexite